Significance of Traumatic Macroamputation in Severely Injured Patients. Issue 3 (March 2015) - Delhey, Patrick; Huber, Stephan; Hanschen, Marc; Häberle, Sandra; Trentzsch, Heiko; Deiler, Stephan; van Griensven, Martijn; Biberthaler, Peter; Lefering, Rolf; Huber-Wagner, Stefan
<x xml:space="preserve">Abstract</x> ABSTRACT Treatment of patients with traumatic macroamputations is challenging. The aim of this study is to analyze the significance of this type of injury in TraumaRegister DGU® (TR-DGU) and to depict the rate of formal surgical ablation of the traumatically induced amputation, epidemiologic data, as well as outcome in severely injured patients with amputations. We acquired data from the TR-DGU of the German Trauma Society (DGU). The inclusion criteria for our study were Injury Severity Score (ISS) greater than 9, macroamputation, and available data about the Abbreviated Injury Scale (AIS) code. A total of 48, 908 of 67, 425 patients had an ISS greater than 9 and available data about the AIS code. In total, 926 (1.9%) of 48, 908 patients had an immediate traumatic macroamputation on-scene. Thereof, 298 patients (32.2%) had a macroamputation of the arms, 605 patients (65.3%) had an amputation of the legs, and 23 patients (2.5%) had both. Among them, 457 patients (49.4%) with a macroamputation had monotrauma. In total, 126 patients (13.6%) underwent replantation and 800 patients (86.4%) underwent formal surgical ablation of the traumatically induced amputation. Seventy-six (23.7%) of 321 patients with upper-extremity amputations and 53 (8.4%) of 628 patients with lower-extremity amputations underwent replantation. Mortality in patients with replantation was lower (5.6% vs. 19.6%, P < 0.001). Standardized mortality rate was lower for patients with replantation (0.71, 95% confidence interval, 0.20–1.21 vs. 0.94, 95% confidence interval, 0.80–1.10; P = 0.26). Glasgow Outcome Scale (GOS) was significantly better for patients with replantation (34.0%; GOS score 5) as compared with patients without replantation (20.7%; GOS score 5; P < 0.001). In borderline patients (defined according to the orthopedic damage control principles), 91.5% received formal surgical ablation of the traumatically induced amputation and 8.5% underwent replantation. The rate of formal surgical ablation of the traumatically induced amputation is higher when principles of damage control surgery are applied. The replantation rate in the upper extremity is higher than in the lower extremity. The less ISS and base excess and the higher blood pressure, hemoglobin value, and thromboplastin time are, the safer the decision for replantation seems to be.